ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TARIF PAJAK EFEKTIF PADA PERUSAHAAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Imam Prasetiyo, 12.05.52.0103; Maryono, Maryono (Students' Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of: Capital Intensity Ratio, Independent Commissioner, debt level, profitability, and the size of the company, using agency theory. Because tax planning will trigger many problems that exist in the company, and therefore it can be minimized by the presence of capital intensity ratio, an independent commissioner, debt level, profitability, and firm size. This research is empirical research consisting of a population of some 108 of the company's banking using purposive sampling technique in penganbilan sample. This sampling is done by multiple regression using SPSS for windows version 20:00. The coefficient of determination obtained by the value of Adjusted R Square of 0.185. This means the ability of Capital Intensity Ratio, Independent Commissioner, debt, return on assets, and the size of the Company in explaining Effective Tax Rate (ETR) of 18.5, while the rest of 81.5% (100% - 18.5%) is explained by other variables outside the research model ini.Karena level of significance <0.05 then the Dependent Variables significant effect along the Effective Tax rate.Keywords: Effective Tax Rate, Capital Intensity Ratio, Independent Commissioner, Debt, ROA, Size